KETIDAKPATUHAN HUKUM OLEH PELAKU USAHA TERHADAP PEMBATASAN PERMODALAN ASING PADA SEKTOR APOTEK - Shabrina, Ghina; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: This paper examines the legal non-compliance of business actors regarding foreign capital restrictions in the pharmacy sector. The investment regulations categorize the pharmacy business as a Micro, Small, and Medium Enterprise (MSME), thus limiting it to domestic capital. However, in reality, many business actors violate these provisions by involving foreign capital in their ownership structure. This study employs a normative legal approach, emphasizing the importance of ethical principles, justice, and legal compliance. The conclusion of this writing indicates that this non-compliance is influenced by a complex interaction between substance, structure, legal culture, and external factors. It is recommended that the government enforce the law firmly, enhance the socialization of regulations, and implement effective supervision to promote legal compliance and fair competition in the pharmacy sector. Additionally, an evaluation of investment regulations is necessary to support the growth of businesses in this sector.Keywords: Legal Compliance, Restrictions, Foreign Capital, Pharmacy